Sustainable energy empowerment in remote regions wind-solar system with intelligent management - Rouas, Rabah; Sibrahim, Madjid; Aissou, Said; Haddad, Salah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper presents a device designed to provide continuous electrical energy to isolated areas where connection to the power grid is expensive and unprofitable. This objective is achieved through a system that combines a wind turbine and photovoltaic panels as primary energy sources, with storage batteries and a diesel generator serving as backup sources. The main contribution of this work is characterized by the ability to ensure uninterrupted electrical power supply, even on days when renewable energy sources are less favorable. This intermittency is due to the random nature of these sources, as well as their dependency on weather and climatic conditions. Therefore, we sized each component of the hybrid system to meet the maximum required load individually under the most favorable conditions. We then modeled each energy conversion chain and developed power control laws to ensure effective set point tracking. Finally, we implemented a hierarchical energy management algorithm to define the operating modes of the hybrid system's sources, aiming to produce as much power as the load requires while prioritizing the use of renewable energy sources to minimize reliance on the storage system and the diesel generator.